Orientation Activities Structural Model to Constru Petrochemical Company - Arianto Ariandi; Nugroho BS. Sukamdani; Maya Dewi Diyah Maharani (Budapest International Research and Critics University, 2022)
Petrochemical company contend disruption of talent war to retain best talents. Employee Experience (EX) concept following the success of Customer Experience. Positive EX likely will give more benefits and engaged thus company wants to implement. Structured activities of orientation as one of important aspects in HR management to begin implementing EX. Identify structured model of orientation activities that construct Employee Experience. Methodology: Statistic analysis using SmartPLS Program to result activities model that construct Employee Experience. Only in the first month's feedback has no positive and significant impact on orientation activities that construct EX, but the activities still needed based on survey feedback. Structured orientation activities to construct Employee Experience obtained through descriptive approach and associative analysis using the SmartPLS version 3.0 with the results of orientation preparation, first day of work, first week activities, feedback and evaluation and evaluation of orientation activities has a positive and significant impact on Employees Experience only in the first month's feedback has no positive and significant impact.